Migrated Peripherally Inserted Central Catheter in the Right Ventricle and Bilateral Pulmonary Arteries: A Case Report - Anand, Reena; Dagar, Vineeta; Aggarwal, Rajeev; Batra, Sandeep (Indian Journal of Radiology and Imaging, 2024)
Introduction Central venous catheterization is a common tool widely used in medical treatment for long-term intravenous administration of medication (e.g. chemotherapy or antibiotics) or parenteral nutrition. Here, we present a case of a missing peripherally inserted central catheter (PICC) which was detected on computed tomography (CT) scan thorax.Case Report A 50-year-old female admitted for follow-up for adenocarcinoma rectum was found to have a missing PICC line and advised CT thorax for evaluation. The imaging findings revealed coiled PICC line in the right atrium extending to inferior vena cava and into right ventricle and further extending and coiled PICC is seen in the main, right, and left pulmonary arteries. Through emergency interventional procedure, the PICC line was successfully retrieved percutaneously via the right femoral vein.Conclusion PICC fracture is less common and always seen without significant discomfort if not found timely, and it may lead to serious complications, such as pulmonary embolism, and even death. Early detection and removal may help to prevent signiﬁcant mortality.
Keywords: peripherally inserted central catheter; localization; computed tomography; complications; intervention